2021
DOI: 10.1111/jsr.13425
|View full text |Cite
|
Sign up to set email alerts
|

Changes in dream features across the first and second waves of the Covid‐19 pandemic

Abstract: Summary Research during the Covid‐19 pandemic has highlighted its significant impact on dreaming. Here we address changes in dream features both during the first wave, when the Italian government imposed a total lockdown, and the second wave (autumn 2020), when a partial lockdown was effected. In April 2020 (total lockdown), 1,622 participants (M age = 34.1 ± 13.6 years; 1171F) completed an online survey including the Pittsburgh Sleep Quality Index and a set of questions on dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(72 citation statements)
references
References 44 publications
(121 reference statements)
5
64
0
Order By: Relevance
“…Additionally, stable characteristics, i.e., age and gender modulated the oneiric frequency. Indeed, during lockdown women showed greater self-reported dream frequency [12,13,15], and older adults reported lower dream rates [12,15,17]. In addition, nightmares increased during the Italian lockdown [12].…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…Additionally, stable characteristics, i.e., age and gender modulated the oneiric frequency. Indeed, during lockdown women showed greater self-reported dream frequency [12,13,15], and older adults reported lower dream rates [12,15,17]. In addition, nightmares increased during the Italian lockdown [12].…”
Section: Introductionmentioning
confidence: 97%
“…They revealed that significantly fewer participants reported dream changes (frequency, length, and vividness) during the second wave of pandemic, compared with the first. In this view, the authors suggested that people perceived fewer changes in their dreams since their life and daily routine were less impacted by the second, partial, lockdown [17]. Moreover, increased emotional charge was found both during the first and second wave, while subjects reported that dream emotionality returned almost to baseline between the first and second lockdown [17].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Unsurprisingly, in fact, surveys including retrospective questions on the pre-pandemic period have been repeatedly employed in sleep studies conducted during the pandemic (e.g. [7,8,55,56]).…”
Section: Discussionmentioning
confidence: 99%